2017
DOI: 10.1542/peds.2017-2213
|View full text |Cite
|
Sign up to set email alerts
|

Health Equity and Quality of Care Assessment: A Continuing Challenge

Abstract: Opinions expressed in these commentaries are those of the author and not necessarily those of the American Academy of Pediatrics or its Committees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…8 Although we use this framework explicitly for this review, it is important to understand that disparities in care and outcomes may overlap with biologic and socioeconomic factors that may be difficult to untangle. 3 We do not address these important issues in our review. However, there is ample evidence that racial and ethnic minorities have disadvantages across the spectrum of factors identified as representing quality of NICU care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Although we use this framework explicitly for this review, it is important to understand that disparities in care and outcomes may overlap with biologic and socioeconomic factors that may be difficult to untangle. 3 We do not address these important issues in our review. However, there is ample evidence that racial and ethnic minorities have disadvantages across the spectrum of factors identified as representing quality of NICU care.…”
Section: Discussionmentioning
confidence: 99%
“…2 An additional component to racial and/ or ethnic inequity in infant outcomes is differences in NICU quality of care stratified by race and/or ethnicity. 3 Disparities in quality have been found in other areas of health care, including, for instance, cancer care, 4 cardiovascular care, 5 and pediatric care. 6 The advantage of addressing disparities in care delivery is that they are amenable to improvement through quality improvement (QI) methodology, with the potential for spreading solutions at scale with long-term benefit.…”
mentioning
confidence: 99%
“…In a commentary, Lorch 73 noted the challenges of combining health equity goals with the measurement of health care quality in perinatal care. By monitoring indicators stratified by indicators of social determinants (race/ethnicity, insurance, urban/rural), quality improvement collaboratives have the potential to improve health care quality, address health equity, and reduce disparities with thoughtful intent in the appropriate cultural context.…”
Section: Public Health’s Role In the Prevention Of Very Preterm Birthmentioning
confidence: 99%
“…39 Emerging research suggests that current structures and processes in place in health care may disadvantage infants of color cared for in the NICU, especially Black infants. 24,40,41 Many of the poorer outcomes noted in these populations could be mitigated by newer strategies inclusive of infrastructures and processes that support addressing racial and ethnic disparities. 23,42,43 Normalized median login results showed that there were more logins occurring earlier into the hospital stay than later into the hospital stay in the Public Insurance group as compared with the Non-Public Insurance group.…”
Section: Discussionmentioning
confidence: 99%